(untitled) (Ta’limning zamonaviy transformatsiyasi, 2025)
Ted Hughes' poetry is renowned for its profound exploration of the relationship between humans and nature. His works vividly depict nature as a primal, indifferent force, often contrasted with humanity's fragile existence and alienation. This study employs a multidisciplinary framework to analyze Hughes' poetry, incorporating ecocriticism, close reading, psychoanalytic criticism, mythological analysis, and historical contextualization. By examining Hughes’ themes of violence, alienation, and the mirroring of human psyche through nature, the research aims to provide insights into his complex portrayal of the natural world and its broader philosophical and environmental implications. Hughes' poetry challenges readers to rethink humanity's ethical and existential relationship with nature, contributing to both literary scholarship and contemporary ecological discourse.